Blockchain data analytics for dummies - Solomon, Michael (Michael G.), 1963- (John Wiley & Sons, 2020)
Blockchain is about to upend the world of data analytics just as it did financial record-keeping. Here's what you need to become an early adopted of blockchain as a big-data tool! Explore how blockchains store data and learn how this rich new source of data can enhance predictive analytics and real-time data analysis. You'll also find out how blockchains can help you manage your data and keep shared data more secure. Learn to implement blockchain analysis models, use third-party toolsets, assess your analysis needs, and more. -- From publisher's description.